On the genesis of absolute pitch - Makomaska, Sylwia (Interdisciplinary Studies in Musicology, 2018)
The clear majority of people with a professional or amateur contact with music do not possess absolute pitch and get by perfectly well without it, making use of relative musical pitch. Yet many people dream of also fixing in their memory the actual pitches of the notes of the musical scale, which would effectively give them the chance to recognise and reproduce any chromatic pitch (C, C#, D, D#, etc.) without recourse to a reference note. Unfortunately, it almost always proves too late for them to develop absolute pitch. The question of the factors determining the forming of absolute pitch is still the subject of quite heated discussion. Practically from the outset of the interest in the phenomenon of absolute pitch (i.e. from the second half of the nineteenth century) controversial theories arose regarding its origins. In discussion on the subject, there was a clash of two fundamental views, regarding absolute pitch either as an innate ability or, on the contrary, as an ability that could be acquired at any age. With time, there emerged an increasing number of hypotheses accounting for the origin of absolute pitch: from the theory of the limitless possibility of absolute pitch acquisition through the theories of innate factors and of early learning, to the latest theory that links absolute pitch to tonal languages. The present paper shows the results of the research project on the occurrence of absolute pitch among young people in musical education in Poland (1175 pupils, aged 11-29) carried out in the years 2004-2007. The test results (pitch-naming tests) supported by the data from the survey (concerning e.g. musical education, familial aggregation of AP and etc.) are presented in the context of theories which attempt to investigate the source of absolute pitch (especially early musical training theory and genetic factors theory).